Redox-responsive release of active payloads from depolymerized nanoparticles. Issue 14 (25th January 2017) - Lv, Li-Ping; Jiang, Shuai; Inan, Alper; Landfester, Katharina; Crespy, Daniel
Abstract : The difference in the reactivity of two monomers, aniline (ANI) and 2, 5-dimercapto-1, 3, 4-thiadiazole (DMcT), was employed to design nanoparticles with completely different nanostructures. Abstract : The difference in the reactivity of two monomers, aniline (ANI) and 2, 5-dimercapto-1, 3, 4-thiadiazole (DMcT), was employed to design nanoparticles with completely different nanostructures. The monomers were simultaneously polymerized by tandem oxidative polymerization occurring in the miniemulsion droplets. DMcT is also a corrosion inhibitor and its polymer can be depolymerized by reduction, which avoids the unwanted release of the payload DMcT when the capsules are not activated. The redox-responsive release profile of DMcT from the composite particles is controlled by the morphology of the particles and it was investigated for monolithic, multi-hollow, and yolk–shell structures. These PANI/PDMcT composite particles may find potential application in Li–S batteries or in the self-healing systems for corrosion protection.